Estetika Bahasa Emotif dan Deskriptif sebagai Penggerak Emosi dalam Novel Laut Bercerita - Laily Najmi Zahiroh; Aulia Latif; Ikhwan Nur Rois (sarasvati, 2025)
The purpose of this study is to describe and analyze the emotive and descriptive language styles found in the book Laut Bercerita by Leila S. Chudori. This novel not only presents a fictional story, but also depicts the political and social situation in Indonesia before the reformation, especially the kidnapping of activists that occurred from 1997 to 1998. This research was conducted through a qualitative literature study approach and focused on the study of stylistics and literary psychology. Data were collected from novel excerpts containing emotive and descriptive language styles. Furthermore, data analysis was carried out with reference to literary and linguistic theories. The results show that emotive language styles are used to increase the intensity of feelings by depicting trauma, suffering, love, loss, and resistance of characters. Thus, these language styles are able to attract empathy and emotional involvement of readers. However, descriptive language styles use visual, auditory, kinesthetic, and olfactory imagery to show details of the atmosphere, environment, and events in a concrete manner. Both language styles work together to create a poetic, immersive, and meaningful story, while also functioning as a medium for social criticism and a reminder of the nation's history. It is hoped that this research will add to the legacy of stylistic studies and contribute to a better understanding of the role of language aesthetics in contemporary Indonesian literary works. Keywords: Emotive Language Style, Descriptive Language Style, Stylistics, Laut Bercerita, Leila S. Chudori